Ruminant assay for rapidly estimating plant residue decomposability in the field - Tian, G.; Kang, B.; Lambourne, L.J. (1996)
Field litterbag decomposition study, through widely accepted for examining decomposition of plant residues, is time consuming, as it requires several months to complete. An experiment was conducted to explore the possibility to introduce ruminant nylonbag assay which only takes 3-4 days, to plant residue decomposition studies for agricultural purpose. Results showed decomposability of plant residues, measured using the ruminant nylon bag significantly correlated with those using the litterbags, indicating that the ruminant nylonbag assay, widely used for studying herbage breakdown in animal nutrition research, can be used for rapidly estimating the decomposability of plant residues in the field.